Optimalisasi Potensi Wisata Desa Kedungpari Melalui Festival Wisata Kuliner Usaha Mikro Kecil dan Menengah - Hikmah Saptya Ningrum; Sugeng Purwanto (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
Community service program held in Kedungpari Village aims to optimize tourism potential in the village. Through the held of culinary tourism festivals, the potential of Micro, Small Medium Enterprise (MSMEs) that is eminent on the village could be optimized to become Kedungpari Village’s main object of tourism. Accordingly, the culinary tourism festivals are expected to be a tourist destination that is able to appeal tourists to come and visit Kedungpari Village. This study uses qualitative methods of research with a descriptive type of research that focuses on explaining how the process of culinary tourism festivals being held and how it impacted the local communities.